Progression from Pneumonia to ARDS as a Predictor for Fatal COVID-19 - Chen-Yang Hsu; Chao-Chih Lai; Yen-Po Yeh; Chan Chang-Chuan; Hsiu-His Chen (Elsevier, 2021)
There is a serious concern over the variation of case fatality of COVID-19 patients that reflects the preparedness of the medical care system in response to the surge of pneumonia patients. We aimed to quantify the disease spectrum of COVID-19 on which we are based to develop a key indicator on the probability of progression from pneumonia to acute respiratory disease syndrome (ARDS) for fatal COVID-19. The retrospective cohort on 12 countries that have already experienced the epidemic of COVID-19 with available open data on the conformed cases with detailed information on mild respiratory disease (MRD), pneumonia, ARDS, and deaths were used. The pooled estimates from three countries with detailed information were 73% from MRD to pneumonia and 27% from MRD to recovery and the case-fatality rate of ARDS was 43%. The progression from pneumonia to ARDS varied from 3% to 63%. These key estimates were highly associated with the case fatality rates reported for each country with a statistically significant positive relationship (adjusted R2 = 95%). Such a quantitative model provides key messages for the optimal medical resources allocation to a spectrum of patients requiring quarantine and isolation at home, isolation wards, and intensive care unit in order to reduce deaths from COVID-19.